URGENSI PENJAMINAN MUTU LEMBAGA PENDIDIKAN - Moch. Yaziidul Khoiiri (JIEM: Journal of Islamic Education and Manajemen, 2021)
Quality assurance is the process of establishing and meeting quality management standards consistently and sustainably, so that stakeholders get satisfaction. Quality management in education has a very important role to realize quality education and can be in line with international schools. The external quality assurance system aims to ensure the internal quality assurance system and the quality improvement process in the education unit can run well. While its function is to monitor, facilitate, evaluate the fulfillment of national standards in education units, evaluate and develop standards, and establish accreditation of educational units. The form or cycle of external quality assurance can be divided into three groups according to the focus of the task and its authority, namely: the facilitation cycle of quality improvement, the cycle of developing quality standards of primary and secondary education, the Accreditation Cycle of Education Units